1996
DOI: 10.1046/j.1365-2567.1996.506585.x
|View full text |Cite
|
Sign up to set email alerts
|

Venom immunotherapy modulates interleukin‐4 and interferon‐γ messenger RNA expression of peripheral T lymphocytes

Abstract: SUMMARYThe mechanism by which specific immunotherapy exerts its beneficial effect remains unclear. In order to evaluate the influence of venom immunotherapy on the T-cell cytokine pattern of allergic reactions, we studied interleukin-4 (IL-4) and interferon-g (IFN-g) mRNA expression of peripheral T lymphocytes from 12 patients undergoing rush venom desensitization, before treatment at Day 0 (D0), at Day 15 (D15) and Day 90 (D90) after treatment, and from seven controls. Antigen-specific T-cell proliferation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 34 publications
2
37
1
Order By: Relevance
“…Moreover, this study employed culture techniques that necessitated expansion of cells in IL-2 and stimulation with non-specific mitogens. Similar findings have also been reported following rush desensitization for wasp and bee venom anaphylaxis [16][17][18]. In contrast, we did not identify either a reduction in IL-5 or an increase in IFN-g production in PBMC cultures following immunotherapy, despite use of validated methods in a blinded controlled clinical study.…”
Section: Figsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, this study employed culture techniques that necessitated expansion of cells in IL-2 and stimulation with non-specific mitogens. Similar findings have also been reported following rush desensitization for wasp and bee venom anaphylaxis [16][17][18]. In contrast, we did not identify either a reduction in IL-5 or an increase in IFN-g production in PBMC cultures following immunotherapy, despite use of validated methods in a blinded controlled clinical study.…”
Section: Figsupporting
confidence: 84%
“…In support of this hypothesis, Secrist et al [13] observed a reduction in IL-4 production by allergen-specific T cell lines derived from peripheral blood of immunotherapy treated patients relative to untreated controls, and we have previously reported increased expression of IFN-g mRNA in skin and nasal biopsies of successfully treated patients after local allergen provocation [14,15]. A decrease in Th2-type and reciprocol increases in Th1-type cytokine production following high-dose antigen administration have also been described following insect venom desensitization [16][17][18]. A further feature of successful immunotherapy is a macroscopic inhibition of allergen-induced late-phase responses and an attendant reduction in the numbers of infiltrating eosinophils [15,[19][20][21].…”
Section: Introductionmentioning
confidence: 85%
“…These results suggest that cytokine based, allergen-specific immunotherapies with IL-18 may be effective in treating allergic diseases and asthma. Currently, conventional allergen immunotherapy, performed by the s.c. injection of increasing doses of allergen, is the only currently available therapy that alters the underlying pathologic allergen-specific Th2-driven responses, resulting in clinical tolerance to subsequent allergen exposure (10,46). Our results leads us to speculate that IL-18, in conjunction with IL-12, may serve as an effective adjuvant to enhance the efficiency of allergen-based immunotherapies, which might be effective in reversing the symptoms of asthma and allergy.…”
Section: Discussionmentioning
confidence: 81%
“…However, this discrepancy could be explained by the differences in cell-culture conditions (e.g., the use of IL-4, an agent suppressing type 1 responses, in the former study. Similarly, during SIT with inhalant allergens, increased expression of IL-2 and IFN-ymRNA, as well as the presence of intracellular IFN-7 in T cells, was reported (62,65). However, other investigators could not confirm these results, and even decreased IFN-y production after house-dust-mite immunotherapy was reported (63).…”
Section: Modulation Of Thl/th2 Balancementioning
confidence: 99%